Evaluating a community engagement model for malaria elimination in Haiti: lessons from the community health council project (2019–2021) - Kevin Bardosh; Luccene Desir; Lorence Jean; Sarah Yoss; Brianna Poovey; Andrew Nute; Madsen Valerie Beau de Rochars; Marc-Aurèle Telfort; Fabiola Benoit; Ginette Chery; Marie Carmelle Charlotin; Gregory S. Noland (Malaria Journal, 2023)
Abstract Background Community engagement (CE) plays a critical role in malaria control and elimination. CE approaches vary substantially, with more participatory programmes requiring higher levels of adaptive management. This study evaluates the effectiveness of a volunteer-based CE programme developed in Haiti in 2018. The approach was based on local leaders organizing and implementing monthly anti-malaria activities in their communities, and was implemented as part of Malaria Zero Consortium activities. Methods This programme evaluation draws on quantitative and qualitative data collected from 23 Community Health Councils (CHCs) over a two-year period (2019–2021) in Grand’Anse department, a malaria hotspot region in Haiti. Results Monthly monitoring data showed that 100% of the 23 CHCs remained functional over the two-year period, with an average of 0.90 monthly meetings held with an 85% attendance rate. A high degree of transparency and diversity in membership helped create strong planning and involvement from members. CHCs conducted an average of 1.6 community-based activities per month, directly engaging an average of 123 people per month. High levels of fluctuation in monthly activities were indicative of local ownership and self-organization. This included school and church sensitization, environmental sanitation campaigns, mass education, support for case referrals and community mobilization during mass drug administration (MDA) and indoor residual spraying (IRS) campaigns. Members drew on the tradition of konbit (mutual self-help), local histories of health and development campaigns and a lexicon of “solidarity” in difficult times as they negotiated their agency as community volunteers. Small incentives played both symbolic and supportive roles. Some level of politicization was viewed as inevitable, even beneficial. Rumours about financial and political profiteering of CHC volunteers took time to dispel while the tendency towards vertical planning in malaria control created conditions that excluded CHCs from some activities. This generated resentment from members who felt sidelined by the government malaria programme. Conclusion The CHC model was effective in promoting group solidarity and community-based anti-malaria activities over a two-year period in Haiti. With the end of the Malaria Zero Consortium in early 2021, there is now an opportunity to better integrate this programme into the primary healthcare system, evaluate the impact of the CHCs on malaria epidemiology, and promote the greater integration of CHCs with active surveillance and response activities.